Pengaruh Pemberian Dosis Pupuk Cair terhadap Pertumbuhan dan Produksi Tanaman Sawi (Brassica Sinensi L.) dalam Polybag di Kelurahan Nangametin Kecamatan Alok Timur Kabupaten Sikka - Mario Malado; Akbar Saitama (Agriculture - Jurnal Ilmu Pertanian, 2025)
The research on the effect of liquid organic fertilizer dosage on the growth and production of mustard greens cultivated in polybags was conducted in Nangameting Village, East Alok District, Sikka Regency. The purpose of this study was to determine the effect of liquid fertilizer dosage on the growth and production of mustard greens and to identify the appropriate dosage of liquid organic fertilizer that could improve the growth and production of mustard greens. This study used a Randomized Block Design (RBD) with five (5) treatments and four (4) replications, resulting in twenty (20) experimental units, namely: O0 (control/without fertilizer), O1 (300 ml/liquid fertilizer), O2 (600 ml/liquid fertilizer), O3 (900 ml/liquid fertilizer), and O4 (1200 ml/liquid fertilizer). The results showed that the application of liquid organic fertilizer had no significant effect on plant height and fresh weight of mustard greens. However, the placement of polybags in each group significantly affected the number of leaves of mustard plants. The highest average fresh weight was found in treatment O3 with a dosage of 900 ml/polybag, reaching 20.75 cm, while the lowest average was found in treatment O0 without fertilizer, with an average of 11.5 cm.